Force field‐dependent solution properties of glycine oligomers. Issue 17 (7th May 2015) - Drake, Justin A.; Pettitt, B. Montgomery
Abstract : Molecular simulations can be used to study disordered polypeptide systems and to generate hypotheses on the underlying structural and thermodynamic mechanisms that govern their function. As the number of disordered protein systems investigated with simulations increase, it is important to understand how particular force fields affect the structural properties of disordered polypeptides in solution. To this end, we performed a comparative structural analysis of Gly3 and Gly10 in aqueous solution from all atom, microsecond molecular dynamics (MD) simulations using the CHARMM 27 (C27), CHARMM 36 (C36), and Amber ff12SB force fields. For each force field, Gly3 and Gly10 were simulated for at least 300 ns and 1 μs, respectively. Simulating oligoglycines of two different lengths allows us to evaluate how force field effects depend on polypeptide length. Using a variety of structural metrics (e.g., end‐to‐end distance, radius of gyration, dihedral angle distributions), we characterize the distribution of oligoglycine conformers for each force field and show that each sample conformation space differently, yielding considerably different structural tendencies of the same oligoglycine model in solution. Notably, we find that C36 samples more extended oligoglycine structures than both C27 and ff12SB. © 2015 Wiley Periodicals, Inc. Abstract : The number of disordered protein systems investigated with simulations continues to increase. While many classical force fields model structured proteins well, it is important to understand how force fields affect structural properties when extended to modeling highly disordered polypeptides. To this end, a comparative structural analysis of Gly3 and Gly10 in aqueous solution from all‐atom, microsecond MD simulations using the CHARMM 27 (C27), CHARMM 36 (C36), and Amber ff12SB force fields was performed.